Topographic Mapping of P300 and Frontal Cognitive Function in Parkinson’s Disease - Mutsumi Iijima; Mikio Osawa; Makoto Iwata; Akiko Miyazaki; Hideaki Tei (Behavioural Neurology)
The purpose of this study was to evaluate the relationship between P300 that is one of the event-related potentials and frontal cognitive functions in Parkinson’s disease (PD) without clinically apparent dementia.